Webalyt: Open Web Analytics Platform - Čegan, Lukáš; Filip, Petr (IEEE (Institute of Electrical and Electronics Engineers), 2017)
Web analytics tools offer important support for better recognition of the web user's behavior, identify bottlenecks and errors in user interface design, measure performance of web environment, monitor website availability or recommend appropriate website content. These tools are based on tracking techniques and sophisticated algorithms that process and evaluate large volumes of captured data. In this paper, we propose a new open web analytics platform called Webalyt that is designed with regard to ensuring availability and reliability under high traffic. A presented platform is formed by interconnected components, which apart from providing the basic functionality of tracking systems, also features advanced functionality for processing real-time data which is needed for recommendation systems. Furthermore, the platform has a scanning robot to search for information about users of third-party applications and marketplace for data interchange between trading partners. The platform is an open source with documented APIs for the development of expansion modules.
Webalyt: Otevřená Analytická Webová Platforma
Keywords: web analytics; website; monitoring; user behavior; error handling; Analýza webu; web; monitoring; uživatelské chování